2011
DOI: 10.1007/s11133-011-9193-1
|View full text |Cite
|
Sign up to set email alerts
|

Class Reproduction by Four Year Olds

Abstract: While scholars know that young children are active if inadvertent participants in social reproduction, little has been said about how young children engage in class reproduction. Through observing in a preschool classroom with a class diverse student body, I show that preschoolers are already class actors, performing class through their linguistic styles. Upper-middle-class children speak, interrupt, ask for help, and argue more often than working-class children. Upper-middle-class children's classed linguisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 22 publications
1
69
0
5
Order By: Relevance
“…Lareau (2003) observes that middle-class parents teach their children to be assertive, take initiative, and negotiate with authority, whereas working-class parents teach their children to hold back their opinions and defer to authority (see also Kohn 1969). As a result, middle-class children are better able than working-class children to customize interactions to their benefit, for example, by gaining additional assistance from teachers (Calarco 2011, 2014; Streib 2011) or by getting a doctor to attend to their concerns (Lareau 2003). “In a historical moment when the dominant society privileges active, informed, assertive clients of health and educational services,” Lareau (2002:794) argues, “the strategies employed by children and parents are not equally effective across classes.” For Lareau, these interactional skills are symbolic; they are evaluated favorably in a particular time and place.…”
Section: Cultural Skills and Inequalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lareau (2003) observes that middle-class parents teach their children to be assertive, take initiative, and negotiate with authority, whereas working-class parents teach their children to hold back their opinions and defer to authority (see also Kohn 1969). As a result, middle-class children are better able than working-class children to customize interactions to their benefit, for example, by gaining additional assistance from teachers (Calarco 2011, 2014; Streib 2011) or by getting a doctor to attend to their concerns (Lareau 2003). “In a historical moment when the dominant society privileges active, informed, assertive clients of health and educational services,” Lareau (2002:794) argues, “the strategies employed by children and parents are not equally effective across classes.” For Lareau, these interactional skills are symbolic; they are evaluated favorably in a particular time and place.…”
Section: Cultural Skills and Inequalitymentioning
confidence: 99%
“…Researchers, however, argue that part of classroom competence is the ability to interpret different contexts and activate skills and behaviors at appropriate times (Mehan 1980). Instead of always raising their hands, middle-class students learn when to raise their hands, when to call out, and when to approach their teachers for help based on their interpretation of the situation (Calarco 2011; Streib 2011). …”
Section: Producing Worker-learnersmentioning
confidence: 99%
“…Consider the practical knowledge required to speak for oneself in the classroom: audibility is critical to getting attention in loud and populated public school classrooms, yet the skills for making oneself heard are unevenly distributed across class lines (Calarco 2011;Streib 2011;also Condron 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that preschoolers readily make social class distinctions and articulate differences between rich and poor (Ramsey, 1991). Four-year-olds also perform social class in preschool settings, primarily through distinct linguistic styles resulting in greater opportunities to develop language skills for higher-SES children (Streib, 2011). These findings have implications for both the cognitive and behavioral domains.…”
Section: Discussionmentioning
confidence: 99%